2014
DOI: 10.9790/0853-13553438
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Foramen Vesalius in Adult Human North Indian Crania

Abstract: Foramen Vesalius is a small, variable and an inconstant foramen located in the greater wing of sphenoid, anteromedial to the foramen ovale, in the middle cranial fossa. This foramen is also known as emissary sphenoidal foramen as it transmits a small emissary vein which drains Cavernous sinus. The importance of this foramen lies in the fact that an infected thrombus from an extracranial source may reach cavernous sinus. The present study was undertaken to observe the incidence of foramen Vesalius in the adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
1
13
2
Order By: Relevance
“…Total distribution of this foramen was lower in the studies done by various authors [7][8][9][10][11][12][13][14][15][16][17][18] as compared to present study as shown in [Table/ Fig-11]. …”
Section: Resultscontrasting
confidence: 34%
See 2 more Smart Citations
“…Total distribution of this foramen was lower in the studies done by various authors [7][8][9][10][11][12][13][14][15][16][17][18] as compared to present study as shown in [Table/ Fig-11]. …”
Section: Resultscontrasting
confidence: 34%
“…The components of the skull base are derived from neural crest cells and mesoderm during the fourth week of fetal life to form the cartilaginous and bony components of the cranial base [5]. Before Gupta et al, [7] 2014 34% 14% 20%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the ESF occurred in 40% of the skulls (21.5% bilaterally, 18.5% unilaterally -7% on the right and 11% on the left side), but no statistically significant difference was detected. Variability existed regarding to the bilateral and unilateral appearance and the side of occurrence [4,12,25,28,30]. Several proposals highlighted the variability of the ESF presence owing to ethnic differences, evolutionary processes [32] and the fact that the ESF represents the site of fusion between the membrane bone and ala temporalis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Following the years, several anatomical studies have focused on FO morphology and morphometry and the ESF presence, absence, morphology and morphometry [9,12,21,25,30,33], but only the study of Wood-Jones [42] was referred to the correlation of FO morphology and the ESF presence or absence. Considering the above observations, we decided to investigate FO size in relation to the ESF absence or presence.…”
Section: Introductionmentioning
confidence: 99%